Personalised 3D-Printed Mucoadhesive Gastroretentive Hydrophilic Matrices for Managing Overactive Bladder (OAB) - Zara Khizer; Muhammad R. Akram; Muhammad Azam Tahir; Weidong Liu; Shan Lou; Barbara R. Conway; Muhammad Usman Ghori (MDPI AG, 2023)
Overactive bladder (OAB) is a symptomatic complex condition characterised by frequent urinary urgency, nocturia, and urinary incontinence with or without urgency. Gabapentin is an effective treatment for OAB, but its narrow absorption window is a concern, as it is preferentially absorbed from the upper small intestine, resulting in poor bioavailability. We aimed to develop an extended release, intragastric floating system to overcome this drawback. For this purpose, plasticiser-free filaments of PEO (polyethylene oxide) and the drug (gabapentin) were developed using hot melt extrusion. The filaments were extruded successfully with 98% drug loading, possessed good mechanical properties, and successfully produced printed tablets using fused deposition modelling (FDM). Tablets were printed with varying shell numbers and infill density to investigate their floating capacity. Among the seven matrix tablet formulations, F2 (2 shells, 0% infill) showed the highest floating time, i.e., more than 10 h. The drug release rates fell as the infill density and shell number increased. However, F2 was the best performing formulation in terms of floating and release and was chosen for in vivo (pharmacokinetic) studies. The pharmacokinetic findings exhibit improved gabapentin absorption compared to the control (oral solution). Overall, it can be concluded that 3D printing technology is an easy-to-use approach which demonstrated its benefits in developing medicines based on a mucoadhesive gastroretentive strategy, improving the absorption of gabapentin with potential for the improved management of OAB.